Approaches to Improve Endometrial Receptivity in Case of Repeated Implantation Failures - Makrigiannakis, Antonis; Makrygiannakis, Fanourios; Vrekoussis, Thomas (Frontiers in Cell and Developmental Biology, 2021)
Repeated implantation failures are a constant challenge in reproductive medicine with a significant impact both on health providers and on infertile couples. Several approaches have been proposed so far as effective; however accumulative data have clarified that most of the treatment options do not have the evidence base for a generalized application to be suggested by the relevant societies. Implantation failures are attributed to either bad quality embryos or to defected endometrial receptivity. The current review aims to summarize in a systematic way all the new trends in managing RIF via interference with endometrial receptivity. The authors focus mainly, but not exclusively, on endometrial injury prior to embryo transfer and endometrial priming with autologous cells or biological agents. To this direction, a systematic search of the Pubmed database has been conducted taking into account the emerged evidence of the last two decades. All the suggested interventions are herein presented and analyzed in terms of reproductive outcomes. It is evident that properly powered and designed randomized trials are needed to support a new standard approach in RIF treatment that will safely be incorporated in national and international guidelines.